Synthesis and Mechanism Study of Carbon Nanowires, Carbon Nanotubes, and Carbon Pompons on Single-Crystal Diamonds - Shuai Wu; Qiang Wang; Kesheng Guo; Lei Liu; Jie Bai; Zhenhuai Yang; Xin Li; Hong Liu (Crystals, 2024)
Carbon nanomaterials are in high demand owing to their exceptional physical and chemical properties. This study employed a mixture of CH4, H2, and N2 to create carbon nanostructures on a single-crystal diamond using microwave plasma chemical vapor deposition (MPCVD) under high-power conditions. By controlling the substrate surface and nitrogen flow rate, carbon nanowires, carbon nanotubes, and carbon pompons could be selectively deposited. The results obtained from OES, SEM, TEM, and Raman spectroscopy revealed that the nitrogen flow rate and substrate surface conditions were crucial for the growth of carbon nanostructures. The changes in the plasma shape enhanced the etching effect, promoting the growth of carbon pompons. The CN and C2 groups play vital catalytic roles in the formation of carbon nanotubes and nanowires, guiding the precipitation and composite growth of carbon atoms at the interface between the Mo metal catalysts and diamond. This study demonstrated that heterostructures of diamond–carbon nanomaterials could be produced under high-power conditions, offering a new approach to integrating diamond and carbon nanomaterials.